Study on the physical properties, anti-aging properties, and rheological characteristics of graphene oxide/rubber powder composite modified asphalt - Wang, Youtao; Sun, Yongzhen; Huang, Lujie; Wang, Xiaofeng; Lin, Chanyuan (Frontiers in Materials, 2026)
IntroductionThe goal of this project is to enhance the construction operability, durability, aging resistance, and high-temperature performance of crumb rubber modified asphalt (CRMA) while encouraging tire recycling in order to meet environmental goals.MethodsTo this end, graphene oxide (GO) is incorporated into the CRMA system to form a GO-CRMA composite material. The modification effects of this composite will be systematically investigated, with the goal of developing a high-performance composite modified asphalt that exhibits outstanding road performance and significant environmental benefits. 70 penetration grade asphalt was selected as the base asphalt (BA); 20% (by mass of BA) crumb rubber was introduced together with GO at dosages of 0.3%, 0.6%, 0.9% and 1.2% (by mass of BA) to produce graphene-oxide/crumb-rubber composite-modified asphalt (GOR). Penetration, softening point, ductility, Brookfield rotational viscosity, and segregation experiments were employed to evaluate physical properties; laboratory simulated aging tests were implemented to evaluate anti-aging performance by analyzing retained-penetration ratio and softening-point increment; and a temperature sweep test revealed high-temperature rheological characteristics of GOR by examining rheological variables like complex modulus (G*), phase angle (δ), and rutting factor (G*/sinδ).ResultsResults show that at a GO dosage of 0.3% the GOR reaches a softening point of 66.3 °C, a ductility 6.9% higher than that of CRMA, a Brookfield viscosity 5% lower, and the minimum segregation softening-point difference; After ageing, it shows the highest level of residual penetration and the lowest softening-point increment; G* and G*/sinδ increase significantly while δ decreases, indicating the best high-temperature rheological performance.DiscussionIn summary, incorporating an appropriate amount of GO can effectively enhance the overall performance of CRMA, with 0.3% identified as the optimal dosage, demonstrating promising prospects for engineering applications.